2023
DOI: 10.3390/plants12061374
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Antifungal, Biosurfactants and Bioemulsifier Activity of Bacillus subtilis subsp. spizizenii—A Potential Biocontrol and Bioremediation Agent in Agriculture

Abstract: In this study, the antifungal, biosurfactant and bioemulsifying activity of the lipopeptides produced by the marine bacterium Bacillus subtilis subsp. spizizenii MC6B-22 is presented. The kinetics showed that at 84 h, the highest yield of lipopeptides (556 mg/mL) with antifungal, biosurfactant, bioemulsifying and hemolytic activity was detected, finding a relationship with the sporulation of the bacteria. Based on the hemolytic activity, bio-guided purification methods were used to obtain the lipopeptide. By T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…However, their application has encountered certain limitations due to their low resistance to extreme conditions of temperatures and pH in modern food technologies. Based on a study by Lima et al [100], a lipopeptide from Candida glabrata demonstrated the ability to successfully reduce the surface tension from ~50 to 28 mN/m and exhibited the capability to maintain emulsions stable over a broad range of temperatures (0-120 • C), pH values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and saline concentrations (2-12%). As a result, biosurfactants have emerged as a promising alternative for several applications.…”
Section: Emulsifying Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their application has encountered certain limitations due to their low resistance to extreme conditions of temperatures and pH in modern food technologies. Based on a study by Lima et al [100], a lipopeptide from Candida glabrata demonstrated the ability to successfully reduce the surface tension from ~50 to 28 mN/m and exhibited the capability to maintain emulsions stable over a broad range of temperatures (0-120 • C), pH values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and saline concentrations (2-12%). As a result, biosurfactants have emerged as a promising alternative for several applications.…”
Section: Emulsifying Activitiesmentioning
confidence: 99%
“…In the case of the lipopeptide-derived Bacillus altitudinis, it exhibited reduced antifungal activities beyond 100 • C and at both acidic and basic pH levels [119]. Cheffi et al [26] observed the stability of lipopeptides from Halomonas venusta across various salinity (up to 120 g/L), temperature (4-121 • C) and pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) values by measuring the oil displacement and surface tension.…”
Section: Biosurfactant Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The lipopeptides produced by the marine bacterium B. subtilis subsp. spizizenii MC6B-22 showed broad-spectrum activity against ten phytopathogens of tropical crops at a minimum inhibitory concentration of 400 to 25 µg/mL and with a fungicidal mode of action, demonstrating the potential of the MC6B-22 strain as a biocontrol agent for agriculture [140]. The efficacy of Bacillus species associated with plant roots as antifungal biocontrol agents was evaluated.…”
Section: Adjuvants For Plant Pathogen Eliminationmentioning
confidence: 99%